Perbandingan Variasi Power Dalam Proses Laser Engraving Terhadap Hasil Produk Stainless Steel - Purba, Adi Syahputra; Hermawan, Muhammad Ghandy Razzaki; Manurung, Meilani Mandhalena; Stefani, Windy; Dzulfiqar, Mohamad Alif; Gunawan, Leo Van (Journal of Applied Mechanical Technology, 2023)
Marking machining processes using lasers have developed in the industrial world. Having high precision and good final quality is one of the advantages of this laser machine. There is a thermal effect generated in the process, so we must understand the impact of the power applied to the material. Carry out the laser marking process with the engraving method on a stainless steel plate material which is given a variation of strength to observe the difference in the final result of a marking. Make as many as 3 pcs of products for each variation of power parameters. The product that has been produced will also be observed for surface roughness on the marking, which aims to find out how deep the food is from the marking. Observation of the surface roughness of the marking on the product using the Surface Roughness Tester 3 times for each product. The results of the data that have been taken will only be observed and entered into the marking results into the roughness class according to ISO or DIN 4763:1981. The marking process uses power variations of 20%, 40%, 60%, 80% and 100%. The results of the marking with the lowest power of 20% produce markings with a roughness value of 0.029µm – 0.110µm and enter into class N3 while the results of marking with the greatest power of 100% obtain a roughness value of 18.210µm – 19.876µm which is included in the roughness class N10. Based on the data obtained in the engraving process with different power variations, it can be interpreted that the higher the power supplied, the higher the roughness value